Gorlin-Goltz Syndrome and Neoplasms: A Case Study - Lopes, Nilza N. F.; Caran, Eliana M.; Lee, Maria Lucia; Silva, Nasjla Saba; Rocha, Andre Caroli [UNESP]; Macedo, Carla R. D. (Journal Pedodontics Inc, 2010)
Gorlin syndrome is a rare autosomal dominant disorder exhibiting high penetrance and variable expressivity. It is characterized by facial dysmorphism, skeletal anomalies, multiple basal cell carcinomas, odontogenic keratocysts (OKC), palmar and plantar pits, bifid ribs, vertebral anomalies and a variety of other malformations. Various neoplasms', such as medulloblastomas, meningiomas, ovarian and cardiac fibromas are also found in this syndrome. Objective: To describe a twelve-year-old patient with Gorlin-Goltz syndrome, with basal cell carcinomas and promyelocytic leukemia developed after receiving craniospinal radiation for a medulloblastoma. Mild ribs as well as mandibular and maxillar OKC were also diagnosed. Conclusion: The patient with Gorlin-Goltz syndrome should receive close follow-up for early detection of malformations and malignant neoplasias.
Keywords: Gorlin syndrome; odontogenic keratocysts; basal cell carcinoma; medulloblastoma; acute myeloid leukemia